Wawasan Al-Qur’an Tentang Etika Eksplorasi Pertambangan - Iin Yuniarni; Nur Arfiyah Febriyani (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2019)
Mining exploration ethic discourse is a thought initiation that is started to be explained since human activity has a global effect toward life. Epistimologically, Its concept is also a confromity initiation ecofenomenology-bassed ethic with qualitative analytical philosophy approach (methaetic). Since it’s related with the Qur’an, then, it added a thematic exegesis approach (maudhu’i), so its main idea revealed behind literal meaning and being equipped with scientic, academic, argumentative and proportional signs. The author in this paper observes that a well and Qur’anic-inline expolation behavior in mining occurs not on a coercon process, yet, based on conciousness of human intersependency sense. As a result, theofanic methaethic intentionality relation which is formulated into the mining exploration ethic in Qur’anic perspective has a harmonious, justice and synergetic mission, as a holistic and integralistic manifestation of humans role in explorating, utilizing, and protecting mining resources through out 6-i (six-i) formulation: istima’r/result orientation, iradah/independent, irtibâtha/connectivity, ihsan/preferable, itqan/optimistic danIltizam/ consistent.